Voyages of discovery : AD 1400-1500 - Time-Life Books (Amsterdam : Time-Life Books, 1991)
1. World history--AD 1400-1500.
Includes bibliographical references.
Bibliography: p. 170-171.
Basic Ed. Students
Keywords: Discoveries in geography; Geography -- Early works to 1800.